Pengaruh Komunikasi Pemasaran Terpadu Terhadap Niat Muzakki Membayar Dana Zakat, Infaq, Shadaqah Pada Yayasan Nurul Hayat Cabang Tuban - Fiqhyany, Milla Rahma; Prasetyo, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aimed to find out the effect of integrated marketing communication whichÂ consist of advertising, public relation, direct marketing, and personal selling to muzakkiâsÂ intention paying zakah, infaq, shadaqah funds at Nurul Hayat Foundation Branch Tuban.Â Primary data of this research is taken by questionnaires with samples are 98 respondent isÂ taken by simple random sampling. This research uses quantitative approach with multipleÂ linear regresion analysis.The result of this research showed that integrated marketing communication(advertising, public relation, direct marketing, and personal selling) simultaneously influenceÂ muzakkiâs intention. While partially, only two variables that are advertising and public relationÂ have influence to muzakkiâs intention. And exogenous variables which is the most dominantÂ influence endogenous is public relation.Nurul Hayat Foundation branch Tuban should give more attention to each kind ofintegrated marketing communication, especially personal selling. Beside that, they shouldÂ give more motivation and training for their employees which work as zakah advisor. ForÂ further research, it can be research about marketing mix is done by a kind of the otherÂ institution, with the result that will find out more extensive research about factors thatÂ influence muzakki pay or distribute zakah, infaq, shadaqah funds at zakah institution.